QUALITY EXAMINATION OF PRIMULA ACAULIS HILL. TREATED WITH TWO DIFFERENT FERTILIZERS - Margarita Davitkovska; Romina Kabranova; Zvezda Bogevska; Gordana Popsimonova; Rukie Agic; Svjetlana Zeljković; Boris Dorbić (My University, 2021)
This research was carried out to analyse the effect of two types of fertilisers on the morphological features of Primula acaulis Hill., as well as to decide on the most appropriate concentration of fertiliser in order to obtain the highest plants quality. Two different types of liquid fertilisers were used in this experiment - Magnicvet and Magnihortal with six treatments. Each treatment comprised 30 plants or a total of 180 plants in the experiment were used. 30 plants per treatment were measured randomly, four months after planting into pots. The following biometric parameters were analysed: plant height (mm), number of leaves, number of flower buds and number of flowers. Measurements of biometric parameters showed that the liquid mineral fertiliser Magnicvet with NPK 7-1-5 + micro elements is more appropriate as compared with the liquid mineral fertiliser Magnihortal with NPK 10-5-5 + micro elements concerning the reinforced nutrition and eventually the enhanced quality of Primula acaulis Hill.. Treatment with Magnicvet 0,4% showed the highest average number of leaves and average number of flower buds, while the treatment with Magnicvet 0,2% showed the highest average plant height and the treatment with Magnicvet 0,3% showed the highest average number of flowers.
Keywords: biometric parameters, fertiliser, Primula acaulis Hill., quality